antibacterial ANTIBAKTERI FRAKSI KLOROFORM BAWANG PUTIH TUNGGAL (Allium sativum L.) TERHADAP Staphylococcus aureus dan Escherichia coli SERTA PENENTUAN SENYAWA AKTIFNYA DENGAN GC-MS - ROKIBAN, AKHMAD; Ramadhan, Gilang; Herdiansah, Riko (JFL : Jurnal Farmasi Lampung, 2023)
Single garlic is one plant that has antibacterial properties. Compounds that act as antibacterial are flavonoids, saponins and allicin.The aim of this study was to prove the antibacterial activity of a single bulb garlic ethanol fraction and to find out the active compound agent which acts as an antibacterial against Staphylococcus aureus and Escherichia coli. The single bulb garlic extraction process was carried out by maceration method using 96% ethanol solvent, the extract continued with the fractionation process with ethanol, n-hexane and chloroform solvents.  Antibacterial activity testing used paper disc method with a concentration of 15%, 30%, 45%, 60%, 75% and 90%, chloramphenicol positive control and aquadest negative control. Antibacterial test results the largest single bulb garlic ethanol fraction was at a concentration of 90% with a inhibition zone diameter of 8.32 in S. aureus and 9.08 in E. coli. Test the compound content using the GC-MS (Gas Chromatography-Mass Spectrometry) method. The results of the antibacterial test were the largest single garlic chloroform fraction at a concentration of 90% with an inhibition zone diameter of 8.32 in S. aureus while 9.08 in E. coli. GC-MS test results obtained organosulfur DATS compound (Dialyl trisulfide).  Keywords: Allium Sativum L., Staphylococcus aureus, Escherichia coli, GC-MS